Size distribution of aerosol particles produced during mining and processing uranium ore. (June 2016) - Mala, Helena; Tomasek, Ladislav; Rulik, Petr; Beckova, Vera; Hulka, Jiri
Abstract: The aerosol particle size distributions of uranium and its daughter products were studied and determined in the area of the Rožná mine, which is the last active uranium mine in the Czech Republic. A total of 13 samples were collected using cascade impactors from three sites that had the highest expected levels of dust, namely, the forefield, the end of the ore chute and an area close to workers at the crushing plant. The characteristics of most size distributions were very similar; they were moderately bimodal, with a boundary approximately 0.5 μm between the modes. The activity median aerodynamic diameter (AMAD) and geometric standard deviation (GSD) were obtained from the distributions beyond 0.39 μm, whereas the sizes of particles below 0.39 μm were not differentiated. Most AMAD and GSD values in the samples ranged between 3.5 and 10.5 μm and between 2.8 and 5.0, respectively. The geometric means of the AMADs and GSDs from all of the underground sampling sites were 4.2 μm and 4.4, respectively, and the geometric means of the AMADs and GSDs for the crushing plant samplings were 9.8 μm and 3.3, respectively. The weighted arithmetic mean of the AMADs was 4.9 μm, with a standard error of 0.7 μm, according to the numbers of workers at the workplaces. The activity proportion of the radon progeny to 226 Ra in the aerosol was 0.61. Highlights: Aerosol particle size distribution of uranium in the Rožná mine was determined. Samplings were made using cascade impactors at sites with the highest expected levels of dust. The geometric means of the AMAD and GSD were 6.2 μm and 3.9, respectively. In terms of the workers, the weighted arithmetic mean of AMADs was 4.9 μm. The activity proportion of the radon progeny to 226 Ra in the aerosol was 0.61.